‘Autism and the good life’: a new approach to the study of well-being - Rodogno, Raffaele (Journal of medical ethics, 2016)
Medical, psychological, educational and social interventions to modify the behaviour of autistic people are only justified if they confer benefit on those people. However, it is not clear how ‘benefit’ should be understood. Most such interventions are justified by referring to the prospect that they will effect lasting improvements in the well-being and happiness of autistic people, so they can lead good lives. What does a good life for an autistic person consist in? Can we assume that his or her well-being is substantively the same as the well-being of non-autistic individuals? In this paper, we argue that, as it stands, the current approach to the study of well-being is for the most part unable to answer these questions. In particular, much effort is needed in order to improve the epistemology of well-being, especially so if we wish this epistemology to be ‘autism-sensitive’. Towards the end of the paper, we sketch a new, autism-sensitive approach and apply it in order to begin answering our initial questions.